Access for all? Assessing vertical and horizontal inequities in healthcare utilization among young people in northern Sweden. Issue 1 (February 2019) - Wagenius, Cecilia M.; San Sebastián, Miguel; Gustafsson, Per E.; Goicolea, Isabel
Background: Previous studies in Sweden have detected socioeconomic inequities in access to healthcare services. However, there is limited information regarding access in younger populations. The aim of this study was to explore vertical and horizontal inequities in access to healthcare services in young adults in the north of Sweden. Methods: The study used data from the Health on Equal Terms survey (age group 16–24 years, n = 2726) for the health and healthcare variables and from national registers for the sociodemographic characteristics. Self-rated healthcare utilization was measured as visits to general practitioners, youth clinics and nurses. Crude and multivariable binomial regression analysis, stratified by sex, was used to assess vertical equity, adjusting for sociodemographic characteristics, and horizontal equity, adjusting for need variables. Results: Vertical inequity was detected for all three healthcare services (youth clinics, general practitioners and nurses), with variations for men and women. Horizontal inequities were also found for both men and women in relation to all three healthcare services. Conclusions: These findings suggest that both vertical and horizontal inequities in access exist for young people in northern Sweden and that the associations between sociodemographic characteristics and healthcare utilization are complex and need further investigation.